2019
DOI: 10.1111/his.13830
|View full text |Cite
|
Sign up to set email alerts
|

Differential clinical impacts of tumour budding evaluated by the use of immunohistochemical and haematoxylin and eosin staining in stage II colorectal cancer

Abstract: Aims The aim of this study was to clarify the quantitative and qualitative differences in tumour budding identification between haematoxylin and eosin (H&E) staining and immunohistochemical (IHC) staining for cytokeratin, and to estimate the respective clinical impacts in stage II colorectal cancer. Methods and results We retrospectively examined 314 surgically resected cases of stage II colorectal cancer, and assessed tumour budding on serial section slides with H&E staining and IHC staining for cytokeratin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…For patients with stage II and III CRC, the nuclear expression of maspin has been demonstrated to predict sensitivity to 5-fluorouracil and levamisole (9,12,22). In addition to the findings of the present study, it can be postulated that patients with MSS-CRCs diagnosed with stage II or III, with high-grade budding and nuclear maspin predominance, involving mainly mesenchymal-type CRCs, may be responders in the case of adjuvant chemotherapy (21). On the other hand, patients with mesenchymal-type CRCs may benefit from anti-EMT-associated agents, which are currently being tested in clinical trials (4,23).…”
Section: Grade Of Tumor Budding -------------------------------------supporting
confidence: 68%
See 1 more Smart Citation
“…For patients with stage II and III CRC, the nuclear expression of maspin has been demonstrated to predict sensitivity to 5-fluorouracil and levamisole (9,12,22). In addition to the findings of the present study, it can be postulated that patients with MSS-CRCs diagnosed with stage II or III, with high-grade budding and nuclear maspin predominance, involving mainly mesenchymal-type CRCs, may be responders in the case of adjuvant chemotherapy (21). On the other hand, patients with mesenchymal-type CRCs may benefit from anti-EMT-associated agents, which are currently being tested in clinical trials (4,23).…”
Section: Grade Of Tumor Budding -------------------------------------supporting
confidence: 68%
“…The present study demonstrated the potential prognostic value of tumor buds, high-grade budding indicating lower OS, decreased disease-free and relapse-free survival, and association with advanced tumor stages and the nuclear localization of maspin (6,8,10,20,21).…”
Section: Grade Of Tumor Budding -------------------------------------supporting
confidence: 55%
“…In conclusion, the results indicate that the general use of supporting cytokeratin staining is not superior to the ITBCC assessment criteria. Other studies comparing cytokeratin(only)-based assessments to H & E-based assessments demonstrated non superiority according to the prognostic value as well [12,13]. Small epithelial structures are straightforward to recognize on cytokeratin, but an elaborate study of experts has shown that the assessment of individual tumor buds using cytokeratin immunohistochemistry has just a moderate level of interobserver agreement, which indicates the issue with cytokeratin staining [14].…”
Section: Discussionmentioning
confidence: 99%
“…Staining. The IHC assays were performed as described by Yamadera et al (30). In brief, the implanted xenograft tumor tissues were excised and fixed with 4% paraformaldehyde for 24 h at room temperature, dehydrated using a graded alcohol series of 60, 70, 80, 90, 95 and 100% ethanol and finally embedded in paraffin.…”
Section: Im M U N Ohistochem Ist R Y a N D Im M U N Of Lu Orescen Cementioning
confidence: 99%